Keunggulan Kompetitif PT MAK Selama Masa Pandemi Covid-19 [PT MAK's Competitive Advantage During the Covid-19 Pandemic] - Enrico, Davin; Tan, Jacob Donald (Universitas Pelita Harapan, 2022)
This research was conducted at a family business in Jakarta, PT MAK, as a business actor in the construction of residential houses and/or shop houses to analyze how PT MAK's strategy is to achieve company performance during the COVID-19 pandemic and identify PT MAK's strategy in achieving excellence. competitive. This research uses a qualitative approach – a single case study – in which the data collection technique uses in-depth interviews with the owner, observations and field notes. Interviews were conducted with 10 informants consisting of 2 owners, 4 employees, 2 clients and 2 partners from this family company. The implication of the results of this study is that members of PT MAK, especially the owners, can find out the company's competitive advantages that can be practiced during this COVID-19 pandemic and beyond so that they can compete with their competitors. Furthermore, it can also use the mini-model theory from the results of this study to compare with other case studies in the same sector, namely contractor services.BAHASA INDONESIA ABSTRACTPenelitian ini dilakukan pada sebuah bisnis keluarga di Jakarta, PT MAK, sebagai pelaku usaha di bidang konstruksi pembangunan rumah-rumah hunian dan/atau ruko untuk menganalisis bagaimana strategi PT MAK dalam mencapai kinerja perusahaan selama masa pandemi COVID-19 serta mengidentifikasi strategi PT MAK dalam mencapai keunggulan kompetitif. Adapun penelitian ini menggunakan metode pendekatan kualitatif – single case study – yang di mana teknik pengumpulan datanya menggunakan wawancara secara mendalam kepada pemilik, observasi dan field notes. Wawancara dilakukan kepada 10 informan yang terdiri dari 2 pemilik, 4 karyawan, 2 klien dan 2 partner dari perusahaan keluarga ini. Implikasi dari hasil studi ini adalah anggota dari PT MAK, khususnya pemilik, dapat mengetahui keunggulan kompetitif perusahaan yang bisa dipraktikkan pada saat masa pandemi COVID-19 ini dan seterusnya agar dapat untuk bersaing dengan kompetitor-kompetitornya. Selanjutnya akademisi juga dapat memanfaatkan mini-model theory dari hasil penelitian ini untuk membandingkan dengan case study lainnya di sektor yang serupa yaitu jasa kontraktor.